Procurement of Ship Materials Through the Shipmate Application using the Material Requirement Planning Method - Oceania, Siti Annisafa; Narantaka, Narantaka; Alfalah, Muhammad; Mutaqin, Yosi; Naufaldi, Raihan; Handayani, Melia; Ma’ruf, Ma’ruf (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The shipyard industry in Indonesia plays a central role in the national economic structure. However, it faces various challenges, one of which is inefficient material management. This research explores the material management system at PT Merpati Marine Service with the aim of enhancing operational efficiency. The research method employed is a field study combining observation techniques, interviews, and literature analysis. Data collected are presented through flowcharts and qualitative analysis. The findings indicate that the material management system at PT Merpati Marine Service is still bound by conventional methods, leading to dependence on manual and computer processes, resulting in delays in material procurement and increased costs. To address this issue, the research proposes the implementation of an Application-based Material Requirement Planning (MRP) system. It is expected that this system will minimize dependence on manual and computer processes, expedite material procurement processes, enhance data accuracy, facilitate interdepartmental communication, and reduce material wastage.The implementation of the application-based MRP system is anticipated to enhance material management efficiency at PT Merpati Marine Service, ultimately positively impacting product quality, cost control, and profitability.